Development of Cortical Bone Geometry in the Human Femoral and Tibial Diaphysis. Issue 5 (27th March 2013) - Gosman, James H.; Hubbell, Zachariah R.; Shaw, Colin N.; Ryan, Timothy M.
ABSTRACT Ontogenetic growth processes in human long bones are key elements, determining the variability of adult bone structure. This study seeks to identify and describe the interaction between ontogenetic growth periods and changes in femoral and tibial diaphyseal shape. Femora and tibiae (n = 46) ranging developmentally from neonate to skeletally mature were obtained from the Norris Farms No. 36 archeological skeletal series. High‐resolution X‐ray computed tomography scans were collected. Whole‐diaphysis cortical bone drift patterns and relative bone envelope modeling activity across ages were assessed in five cross‐sections per bone (total bone length: 20%, 35%, 50%, 65%, and 80%) by measuring the distance from the section centroid to the endosteal and periosteal margins in eight sectors using ImageJ. Pearson correlations were performed to document and interpret the relationship between the cross‐sectional shape (Imax/Imin), total subperiosteal area, cortical area, and medullary cavity area for each slice location and age for both the femur and the tibia. Differences in cross‐sectional shape between age groups at each cross‐sectional position were assessed using nonparametric Mann‐Whitney U tests. The data reveal that the femoral and tibial midshaft shape are relatively conserved throughout growth; yet, conversely, the proximal and distal femoral diaphysis and proximal tibial diaphysis appear more sensitive to developmentally induced changes in mechanical loading. Two time periods of accelerated change are identified: early childhood and prepuberty/adolescence. Anat Rec, 296:774–787, 2013. © 2013 Wiley Periodicals, Inc.